We`re not superhuman, we`re human: a qualitative description of elite athletes` experiences of return to sport after childbirth - Davenport, M. H.; Ray, L.; Nesdoly, A.; Thornton, J.; Khurana, R.; McHugh, T.-L. F. (Sports Medicine, 2023)
Background A growing number of athletes return to elite sport following childbirth. Yet, they face significant barriers to do so safely and successfully. The experiences of elite athletes returning to sport following delivery are necessary to support evidence-informed policy.